Hydrolysis Activity of Virgin Coconut Oil Using Lipase from Different Sources - T. A. V. Nguyen; Truong D. Le; Hoa N. Phan; Lam B. Tran (Scientifica)
Two types of lipase, Candida rugosa lipase (CRL) and porcine pancreas lipase (PPL), were used to hydrolyze virgin coconut oil (VCO). The hydrolysis process was carried out under four parameters, VCO to buffer ratio, lipase concentration, pH, and temperature, which have a significant effect on hydrolysis of lipase. CRL obtained the best hydrolysis condition at 1 : 5 of VCO to buffer ratio, 1.5% of CRL concentration, pH 7, and temperature of 40°C. Meanwhile, PPL gave different results at 1 : 4 of VCO to buffer ratio, 2% of lipase concentration, pH 7.5, and 40°C. The highest hydrolysis degree of CRL and PPL was obtained after 16 hours and 26 hours, reaching 79.64% and 27.94%, respectively. Besides, the hydrolysis process was controlled at different time course (every half an hour) at the first 4 hours of reaction to compare the initial hydrolysis degree of these two lipase types. FFAs from hydrolyzed products were isolated and determined the percentage of each fatty acid which contributes to the FFAs mixture. As a result, medium chain fatty acids (MCFAs) made up the main contribution in composition of FFAs and lauric acid (C12) was the largest segment (47.23% for CRL and 44.23% for PPL).